Genetic divergence in commercial cucumber (Cucumis sativus L.) genotypes (Bangladesh Journal of Botany, 2018)
Genetic diversity in commercial cucumber genotypes was estimated based on 13 characters. Path analysis revealed that fruits/plant (0.701) and fruit weight (0.379) had maximum positive direct effect on yield. Seven cucumber genotypes were grouped into three different clusters. The highest inter-cluster distance (4.078) was observed between cluster I and II whereas lowest inter-cluster distance (1.011) was observed between the clusters I and III. Cluster II showed highest mean for length of main vine, nodes/plant, primary branches/plant, days to 1st male flowering, length of internodes/plant, fruits/plant and yield/plant whereas cluster III produced highest mean for leaf length, leaf breadth, fruit length, fruit diameter and fruit weight. Cluster II and III contributed 53.85 and 38.46%, respectively towards divergence.